Case report: Spontaneous remission of severe aplastic anemia mediated by mutant hematopoietic stem cells evading T-cell attack - Shiroshita, Kohei; Zaimoku, Yoshitaka; Kudo, Himari; Obara, Naoshi; Hosomichi, Kazuyoshi; Kano, Yui; Kobayashi, Miku; Morishita, Eriko; Takamatsu, Hiroyuki; Toyama, Takaaki; Nakao, Shinji (Frontiers in Immunology, 2025)
T-cell-mediated severe aplastic anemia (SAA) is typically fatal without prompt hematopoietic stem cell transplantation or intensive immunosuppressive therapy. Although rare cases of spontaneous remission have been reported, the underlying mechanisms remain poorly understood. A 24-year-old woman was incidentally found to have mild pancytopenia during a routine workplace health checkup. Over the subsequent 12 months, her pancytopenia gradually worsened, resulting in exertional dyspnea, purpura, and a diagnosis of SAA. Remarkably, her blood counts began to improve spontaneously 11 days after the diagnosis without any treatment or transfusions. She no longer met the criteria for SAA by day 27 and achieved complete hematologic normalization within three months. At 22 months, flow cytometry and targeted sequencing revealed that 69% of her granulocytes lacked the HLA-A*02:01-C*03:04-B*40:02-DRB1*14:54 haplotype due to acquired loss of heterozygosity, while 23% were glycosylphosphatidylinositol-deficient owing to PIGA mutations. Retrospective digital polymerase chain reaction of diagnostic bone marrow demonstrated that nearly all non-lymphoid cells had already been replaced by HLA allele-lacking clones, whereas glycosylphosphatidylinositol-deficient erythrocytes constituted only 0.25%. These findings suggest that hematologic recovery occurred through the selective expansion of mutant hematopoietic stem cells capable of evading persistent T-cell-mediated destruction. Early identification of HLA allele-lacking leukocytes may help predict spontaneous remission and avoid unnecessary intensive therapy in patients with SAA.